Advancing a Viable Global Climate Stabilization Project: Degrowth versus the Green New Deal. (June 2019) - Pollin, Robert
This paper summarizes a global Green New Deal program that can advance climate stabilization as well as rising mass living standards and an expansion of decent job opportunities. The core features of this program are massive global investments in energy efficiency and clean renewable energy so that clean energy supplants the existing fossil-fuel-dominant global energy system. Through annual investments in the range of 2 percent of global GDP in clean energy and a corresponding contraction in fossil fuel consumption, the global economy can maintain an absolute decoupling trajectory—i.e., economic growth proceeds while CO2 emissions fall to zero within 30–40 years. The paper also shows that a steady contraction of global GDP—i.e., "degrowth"—does not provide a viable climate stabilization framework. JEL Classification: Q54, Q56, Q58